The Potential of Walnut Oil with Massage Effleurage to Prevent Grade 1 Decubitus Wounds of Bed Rest Patients - Iis Noventi; Umdatus Soleha; Siti Nur Hasina (Journal of Ners and Midwifery, 2021)
The main problem in decubitus patients is the risk of damage to skin integrity related to factors: immobility, decreased sensory perception, decreased tissue perfusion, decreased nutritional status, friction and pulling force, advanced age, and increased humidity. The decubitus is a problem faced by patients with chronic diseases, weak conditions, and patients who experience paralysis. This study aimed to analyze the potential of walnut oil in preventing grade 1 decubitus Wounds of bed Rest Patients. This study used a Quasi-Experimental design (pretest-posttest control group). The sample was 20 people, divided into 2 groups; treatment and control. The treatment group received effleurage massage with walnut oil given twice a day for 7 days, while the control group received pressure ulcers prevention treatment according to the SOP applied in the hospital. A total of 10 patients who received massage using walnut oil showed a p-value of 0.04 (<0.05), which meant that walnut oil massage was affected significantly in preventing pressure ulcers. In conclusion, decubitus wounds can be prevented by effleurage massage with walnut oil which is given regularly twice a day.